Deflection analysis of underpinned secant pile wall - Mardi, Marini (2013)
Underpinned retaining wall commonly been used for the construction of underground basement or any other open cut excavation projects, especially in urban areas. The excavation process at a different ground level induced the deflection of the retaining wall. Factors that influence the deformations of retaining wall are the excavation length, excavation depth, wall penetration depth, stiffness of the wall, stiffness of struts, struts spacing, struts preloaded and time dependent. The project focuses on the horizontal movement of the braced retaining wall due to lateral load. The analyses of horizontal deflection are by the beam on elastic foundation (BEF) method (manual calculation) and by the finite-element method (Plaxis v7.2 software). Mohr-Coulomb model is applied in the analysis using Plaxis v7.2. Comparisons are being made on both methods with the secant pile wall field measurement.